Digestão e metabolismo de suínos de diferentes genótipos com ou sem restrição alimentar - Sartor, Cláudio André (2005)
An experiment was carried out to evaluate the digestion and metabolism of different genotypes pigs fed with or without restriction. Twenty-four barrows of three commercial genotypes were utilized, with 47.95 kg initial body weight, housed in metabolic cages maintained in semi-acclimatized atmosphere. A 3 x 2 factorial design was utilized (3 commercial genotypes Agroceres, Dalland, Embrapa, with or without feed restriction), with four replications, being the animal the experimental unit. The genotypes and feed restriction did not influence (P>0.05) dry matter digestibility, crude protein, ether extract and metabolizable energy. However, a 20% restriction related to ad libitum decreased 17% of intake, 11% of fecal losses and 21% of phosphorus absorption. In the nitrogen balance, feed restriction decreased (P<0.05) 20% of urinary excretion, 17% of fecal losses and 19% of retention. The commercial genotypes studied have similar digestibility, energy metabolizibility and nitrogen balance. Feed restriction at 20% level did not affect nutrient digestibility and energy metabolization.